Pelaksanaan Putusan Arbitrase Internasional terhadap Penetapan Kepemilikan Pulau Scarborough Shoal di Laut Cina Selatan - Dessy Kartika Sari; Levina Yustitianingtyas (Faculty of Law Hang Tuah University, 2018)
The South China Sea dispute on the Scarborough Shoal Island, basically caused by the claims of the Chinese nation over the region. The Philippines formally submit the case to Permanent Court of Arbitration (PCA), The Tribunal’s decision in favor of the Philippines and China neither accepting in these decision. The Tribunal’s decision inflicting several legal consequences for China and Philippines. The method used is a normative juridical method and using United Nations Convention on the law of the Sea (UNCLOS) 1982. The Tribunal’s decision is not executed can be a means of pressure for China to be more flexible and accepting in these decisions. In the manner of China neither accepting The Tribunal’s decision, The Philippines could bring the case to the International Tribunal for the law of the Sea (ITLOS) which is an independent judicial International Law of the Sea. Their decision will be final and binding on the parties to the dispute and obliged to obey in these decisions so that the dispute can be resolved peacefully and not inflicting a negative impact on China and Philippines.